Program For Developing Literation Abilities For Early Children In Pandemi Era Covid-19 In The Village Of Kempek Kecamatan Gempol, Cirebon - Amalia Zubaedah, Putri (Green Publisher Indonesia, 2019)
The development of literacy in children is closely related to the ability to read and write. This research is motivated by the large number of early childhood children in primary school education who cannot read and write, where when the child is 7 years old, they should understand and understand letters or numbers, by reading, counting and writing. This research method uses qualitative methods with data collection techniques using interviews and documentation. The result of this research is that the development of literacy for children in the Covid-19 era can be done through tutoring forums, starting from learning to recognize letters, numbers, hijaiyah letters, drawing and so on. This can help children under 7 years of age to quickly recognize letters and so on. This development goal does not only affect literacy, but can foster self-confidence, love friends, and help others. With the tutoring (tutoring) can increase children under the age of 7 who managed to read and write properly and correctly.